The breakfast club [videorecording (DVD)] - Hughes, John, 1950-2009; Estevez, Emilio, 1962-; Gleason, Paul, 1939-2006; Hall, Anthony Michael; Nelson, Judd; Ringwald, Molly; Sheedy, Ally (Universal Studios Home Entertainment, 2015)
Five high school students-- a Rebel, an Athlete, a Brain, a Princess and a Basketcase-- find themselves thrown together serving a Saturday morning detention. They do not have much in common, except giving up their day, sitting in the school library, and writing an essay for the principal. At first, they argue and hate each other, but after smoking some of the Rebel's marijuana, they begin to pour their hearts out to each other. They talk about their fears, secrets, deepest emotions, and problems.